2016
DOI: 10.1186/s12935-016-0315-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of G1-phase cell cycle arrest and apoptosis pathway in MDA-MB-231 human breast cancer cells by sulfated polysaccharide extracted from Laurencia papillosa

Abstract: BackgroundMarine algae consumption is linked to law cancer incidences in countries that traditionally consume marine products. Hence, Phytochemicals are considered as potential chemo-preventive and chemotherapeutic agents against cancer. We investigated the effects of the algal sulfated polysaccharide extract (ASPE) from the red marine alga L. papillosa on MDA-MB-231 human breast cancer cell line.MethodsFlow cytometry analysis was performed to study the cell viability, cell cycle arrest and apoptosis. Changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 61 publications
9
62
1
Order By: Relevance
“…In 4T1.2 mammary tumor cells, administration of A77636 elevated the level of cleaved caspase 3 as a marker of apoptosis12, as well as the level of LC3-phosphatidylethanolamine conjugate (LC3II) as an autophagosome marker13. We have previously reported that salubrinal is capable of inducing cellular death of 4T1 cells as well as MDA-MB-231 cells by elevating p-eIF2α14.…”
Section: Discussionmentioning
confidence: 99%
“…In 4T1.2 mammary tumor cells, administration of A77636 elevated the level of cleaved caspase 3 as a marker of apoptosis12, as well as the level of LC3-phosphatidylethanolamine conjugate (LC3II) as an autophagosome marker13. We have previously reported that salubrinal is capable of inducing cellular death of 4T1 cells as well as MDA-MB-231 cells by elevating p-eIF2α14.…”
Section: Discussionmentioning
confidence: 99%
“…Protein Bcl-2 plays a key role in the regulation of apoptosis in which an increasing Bax/Bcl-2 ratio enhances caspase-3 activity and subsequently induces apoptosis in tumor cells [50]. Phytochemicals seem to have an important regulatory role in Bax/Bcl-2/caspase-3 signaling in breast carcinogenesis [51,52]. In this study, cinnamon caused a significant increase in the Bax/Bcl-2 ratio, which correlated with an increase in caspase-3 expression in treated mammary tumors in rats.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study revealed that sulfated polysaccharide ASPE extracted from Laurencia papillosa inhibits the proliferation of MDA-MB-231 human breast cancer cells by inhibiting the ratio of ROS and Bax/Bcl-2 protein levels in cells (Table 2) [90]. Moreover, carrageenans from the same source inhibited the proliferation and cell viability of MCF-7 human breast cancer cells by the same route in a dose-dependent manner (Table 2) [92].…”
Section: Red Algal Polysaccharidesmentioning
confidence: 99%